Cannabis therapy in neurological disorders: Recent advances and perspectives - Alexandru Mandici; Daniel Cojocariu; Anca Miron (Amaltea Medical Publishing House, 2020)
Both phytocannabinoids (Δ9-tetrahydrocannabinol, cannabidiol) and synthetic derivatives (nabilone, dronabinol) showed therapeutic benefits in some neurological disorders. Cannabis inhalation was reported to attenuate several symptoms (rigidity, bradykinesia, tremor) in Parkinson's disease. A significant reduction in monthly seizures in patients with epilepsy has been noted for cannabidiol, while administration of Δ9-tetrahydrocannabinol resulted in benefits on psychomotor agitation in patients suffering from Alzheimer's disease. Although there are clinical studies supporting the use of cannabis preparations as adjuvant therapy in neurological disorders, more investigations are needed to assess their safety and efficacy.